ETHICAL PROBLEMS OF TECHNOLOGICAL PROGRESS IN THE LIGHT OF THE SOCIAL TEACHING OF THE CATHOLIC CHURCH - Matyukhina Оleksandra (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
The article examines the ethical dimension of technical progress in contemporary society, focusing on transformations in the sphere of labour and their impact on human dignity and social relations. The aims and tasks. The aim of the article is to analyze the social teaching of the Catholic Church regarding ethical challenges caused by technical progress in the sphere of labour. The tasks include identifying key ethical problems and clarifying the principles proposed by the Church for their interpretation. Research methods. The methodological framework includes the methods of analysis and synthesis, as well as systemic and phenomenological approaches, which allow interpreting labour as a fundamental dimension of human existence. Research results. It is shown that in the social teaching of the Catholic Church, labour is understood as a means of self-realisation and social good, while technical progress is interpreted as an ambivalent process that expands human possibilities but also generates new forms of dependency and ethical risks. The Church insists that labour cannot be reduced to a mere factor of production but must be understood as an expression of human creativity and participation in the common good. Discussion. The analysis demonstrates that the Catholic Church emphasizes the necessity of ethical evaluation of technical progress and affirms the priority of human dignity over technique, considering responsibility as a central principle. Conclusions. It is concluded that technical progress is not treated as an end in itself but as a means of human development; however, this ethical framework requires further specification in relation to contemporary forms of technisation of labour.